Blossom-Quad: A non-uniform quadrilateral mesh generator using a minimum-cost perfect-matching algorithm - Remacle, J.-F.; Lambrechts, J.; Seny, B.; Marchandise, E.; Johnen, A.; Geuzainet, C. (International journal for numerical methods in engineering, 2012)
SUMMARY A new indirect way of producing all‐quad meshes is presented. The method takes advantage of a well‐known algorithm of the graph theory, namely the Blossom algorithm, that computes the minimum‐cost perfect matching in a graph in polynomial time. The new Blossom‐Quad algorithm is compared with standard indirect procedures. Meshes produced by the new approach are better both in terms of element shape and in terms of size field efficiency. Copyright © 2012 John Wiley & Sons, Ltd.